1998 Kansas Performance Tests with Alfalfa Varieties - Roozeboom, Kraig L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
The Kansas Agricultural Experiment Station established an official alfalfa performance testing program in 1980 to provide Kansas growers with unbiased performance comparisons on alfalfa varieties marketed in the state. Each year, private companies are asked to enter varieties voluntarily at the locations slated for establishment that year. Descriptive information is presented with the results for each test. This information, including soil type, establishment methods, fertilization, pest control, irrigation, harvest dates, and growing conditions unique to that location, can help explain test and/or variety performance. Forage yields were estimated by harvesting four replications of each variety with a plot harvester.
Keywords: Alfalfa; Yields; Environmental factors; Disease; Insects; Kansas